SISTEM REKOMENDASI PEMBELAJARAN PADA E-LEARNING MENGGUNAKAN ALGORITMA CT-PRO - Ummah, Khoirul (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2015)
The progress of information technology in education, especially the use of e-learning in education institutions developed rapidly, SMA 2 Pamekasan was an example of schools that could use elearning. However, the teachers only used to take the value of the test, assignment by the teacher and to access course materials. Therefore, in this research use data that are considered essential to assist teachers measured students’s progress and help students answer the difficult questions. Subjects that used in this e-learning was chemical. Chemical was one subject that was considered difficult by most students. So, this application would help students solve a problems. The algorithm that used in this application was a ct-pro, it was algorithm of association rules to find combinations of data’s relations. The data were the wrong answers of 150 students. Questions consist of 400 numbers and 20 learning materials. In this research, the data was divided into 6, the data from 5 students, 30 students, 60 studenst, 90 students,120 students and 150 students. The results of this reseacrh was if there were more data, the combination formed itemset also be more and more, and the processing time will also be longer. However, if the greater the minimum support was entered, then the combination was formed will be less.